Hybrid material based on magnetic iron oxides and benzotiazol derivatives as magnetic resonance probe - Ferreira, Silviana Corrêa (2020)
The cancer is a complex and in many cases fatal. It affects all tissues of the human body; it is one of the main causes of death in the world. Lung, stomach, liver, cancer and breast cancers are the most common causes of cancer death every year. Breast cancer comprises 23% of all cancers in women, and is considered the leading and most frequent cause of cancer death among women worldwide. Currently, many anticancer drugs have been used clinically successfully for the treatment of various malignancies. However, mild tumors, such as breast cancer, resist most of the clinically available anticancer agents, due to genetic mutations during the course of therapy that affects the uptake or metabolism of anticancer drugs. Since the response of available tumors to anti-cancer chemotherapeutic agents is limited, look for new drugs that are easily accessible with low cost and superior effectiveness. Medicinal Chemistry plays a crucial role in the complete planning, identification, preparation and understanding of the pharmacological and toxicological effects of prototype compounds. It allows the didactic way of elucidating the mechanism of action at the molecular level and the construction of relationships between the chemica l structure and the pharmacological activity, enabling the process of development and optimization of drugs. Some benzothiazole compounds are highly selective and therapeutic, and have antitumor effects in vitro and in vivo, highlighting or compound 2-(4'-aminophenyl)benzothiazole (ABT), which exert nanomolar concentration activity in vitro against breast cancer diseases in humans. This article describes or designs new contrast agents based on ABT and iron oxide for the use of a bioactive compound that can be used as diagnostic tests. The ABT/δ-FeOOH nanocomposites were prepared by grafting (N-(4'-aminophenyl)benzothiazole-2-bromoacetamide) on the surface of the iron surfaces. The FTIR spectra show the presence of contacts that characterize the formation of ABT/δ-FeOOH nanocomposites. The SEM analysis gives the size of the relationship cluster in relation to the color morphology. The theoretical study enabled a better understanding of the interaction of compounds with iron oxide. The DFT-based calculations reinforce the radical capture mechanism of the stabilization of nanocomposites; that is, how Fe 3+ species can accept used electrons from the organic phase. The Molecular Docking study recommends very relevant information for the study of material, predicting how the compound binds to the active site of the PI3K protein, is a protein involved in a diverse set of cellular functions, such as, for example, metabolism, activity and cellular involvement. These proteins have been studied as a target to control and prevent the development of several diseases, such as breast cancer. The study showed that the proposed material shows good stability at the active site of the protein, thus concluding that it is a good candidate for inhibiting enzymes, that characterize the development of breast cancer.